Solar energy : a course of lectures contributed in the 17th International Science School for High School Students sponsored by the Science Foundation for Physics within the University of Sydney, at the University of Sydney, August 26, September 6, 1974 - International Science School for High School Students 1974 : University of Sydney); Messel, H. (Harry), 1922-; Butler, Stuart Thomas; University of Sydney. Science Foundation for Physics (Oxford ; New York : Pergamon Press, 1975)
Nine lectures concerning specialized aspects of solar energy such as thermal conversion, the nature of solar energy, and heat transfer and storage.
Includes bibliographies and index.
Keywords: Solar energy; Solar energy